Analysis of successful water management experiences in Andea region basins - Luis, A. (CONDESAN, 2011)
This study shows that to achieve successful water management in the Andean region, certain conditions must be in place. These conditions are: participation of all involved actors; dialogue and agreement; transparency; access to adequate and timely information; having a bas in approach; articulation of conservation and productive processes; capacity building and local leader ship strengthening.